KALA ROBOT MASUK KELAS IPA: MEMBEDAH KEGAGAPAN DAN KESULITAN GURU SMP DALAM IMPLEMENTASI STEM ROBOTIK - Kurniawan, Noval; Zulirfan; Yennita; Rahmad, Muhammad; Kartika, Sania (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of technology in the digital era necessitates the integration of STEM in education to develop students' 21st-century competencies. Robotics has emerged as a promising teaching media for STEM learning; however, its implementation still faces considerable challenges. This quantitative survey study aims to analyze the difficulties faced by junior high school science teachers in implementing robotics-based STEM learning and to examine whether these difficulties differ significantly based on teaching experience. A total of 27 science teachers in Tualang District, Siak Regency, were selected through purposive sampling. Data were collected using a validated 28-item Likert-scale questionnaire and converted from ordinal to interval scale using the Method of Successive Interval (MSI). Descriptive analysis revealed high levels of difficulty across all variables: Teacher Readiness (Mean = 2.78), Equipment Completeness (Mean = 2.66), and Training & Workshops (Mean = 2.75). The most critical barrier was the availability of media, modules, and budget (Mean = 2.27). Inferential analysis using the Independent Samples t-test (unequal variances assumed) showed no significant difference between junior (<10 years) and senior (≥10 years) teachers (t = −0.962, p = 0.345 > 0.05), with a small effect size (Cohen's d = 0.35). These findings indicate that robotics-based STEM implementation is a structural challenge affecting all teachers regardless of seniority, necessitating systematic support including standard robotics kit procurement, practical instructional modules, and sustained professional development programs.